Antonio Gramsci, Settler-Colonialism and Palestine. Issue 2 (September 2022) - Mayo, Peter
Abstract : This article explores Gramsci's relevance to colonialism with particular reference to the situation in Palestine and the Palestinians. It historically oscillates between the Italy and larger world contexts of Gramsci's time and the Palestinian and larger Arab contexts in more recent times, especially, in the latter case, from the onset of settler colonialism in the Middle East. While it covers a broad range of writings by Gramsci, notably the notes contained in the Prison Notebooks, it provides special attention to his discussion on the Southern Question. It tackles recurring themes in colonial discourse such as those of 'divide and rule' and ideology residing in language besides the ever so pertinent theme of Hegemony. It posits the resonance of appropriated or reclaimed knowledge with a different 'whole way of life' (Raymond Williams). Palestinian society is represented warts and all, with specific strengths and differences highlighted, especially that of country and the city.